ACCEPTANCE AND COMMITMENT THERAPY MODULATES IMMUNEINFLAMMATORY RESPONSES AND NEUROTROPHIC FACTORS HOMEOSTASIS IN ELDERLY STROKE PATIENTS: A RANDOMIZED CONTROLLED TRIAL - Wang, Jing; Gu, Haiyan; Hu, Xiaorong; Zhou, Yanjie; Wu, Lingling (Journal of Medical Biochemistry, 2025)
Objective: This study examined the regulatory effects of Acceptance and Commitment Therapy (ACT) on T lymphocyte subsets, serum inflammatory cytokines, neurotransmitters, and oxidative stress markers in elderly cerebral stroke (CS) patients, providing insights into the multi-dimensional pathophysiological interactions and potential intervention strategies for chronic stroke recovery.Methods: In this randomized controlled trial, 120 elderly stroke patients were allocated to either an ACT group (ACT intervention; n=60) or a routine group (conventional treatment; n=60). Comprehensive assessments were performed to quantify: (1) peripheral T lymphocyte distribution (CD3+, CD4+, CD8+ subsets, and CD4+/CD8+ ratio), (2) serum inflammatory cytokines (IL-1β, IL-6, IL-10, and TNF-α), (3) neurotransmitters (5-HT, NE, BDNF, and IGF-1), and (4) oxidative stress markers (SOD, MDA, CAT, and NO) using flow cytometry, HPLC-ECD, and ELISA. Statistical analyses were conducted with SPSS 22.0.Results: Following treatment, CS patients exhibited reduced CD3+ and CD4+ T-cell levels along with a decreased CD4+/CD8+ ratio, while CD8+ T-cell proportions were elevated (P
Keywords: Cerebral stroke; T lymphocyte subsets; Inflammatory cytokines; Neurotransmitters; Oxidative stress; Acceptance and commitment therapy